The hearts of men [large type] : a novel - Butler, Nickolas (Center Point Large Print, 2017)
Camp Chippewa, 1962. Nelson is the Bugler, sounding the reveille each morning. He's also the target of the camp's bullies. He begins a friendship with Jonathan, and each boy has something to learn from the other. Now Nelson, a scarred Vietnam veteran, is the scoutmaster of Camp Chippewa; Jonathan is a successful businessman whose children attend the camp. When an unthinkable camp event involves Jonathan's grandson, it brings Nelson to the depths-- and limits-- of his selflessness and bravery.